Endodontic remnants are found more than other radiopacities in proposed implant sites - Hamdy A. M. Marzook; Eman A. Yousef; Abeer A. Elgendy (SpringerOpen, 2021)
Abstract Background Foreign bodies may be a cause of concern in dental implant failure. Purpose The aim of the present study was to assess the occurrence and to evaluate the types of radiopacities in dental extraction sites using cone beam computed tomography (CBCT). Materials and methods The incidence, location, and types of radiopacities were evaluated in 180 CBCT scans. Results Different radiopaque structures could be noted in 84 scans. Foreign bodies and remaining roots were frequently seen. Most of the radiopacities were attributed to remaining endodontic filling in upper and lower jaws in 25 scans in different locations. Remaining roots could be detected in 20 scans. Focal and diffuse radiopaque bony lesions were observed in 16 scans. Tissue response in the form of radiolucency could be seen more with endodontic foreign bodies. Tissue reactions to radiopaque filling remnants were seen in 6.11% of cases. Conclusions Foreign body remnants, mostly of endodontic fillings, were frequently seen in CBCT in upper and lower jaws. Evidence of tissue reactions to extraction remnants could be found. Endodontic filling remnants could be seen more in the upper jaw. Thorough examination of implant site for the presence of endodontic foreign body remnants should be stressed. Debridement of the extraction socket should be done carefully in endodontically treated teeth.